1993
DOI: 10.3382/ps.0720643
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Fructooligosaccharide in Diets for Broiler Chickens and Effects on Salmonellae Contamination of Carcasses ,

Abstract: Two similar trials were conducted to evaluate the effects of dietary inclusion of fructooligosaccharide (FOS) on live performance and carcass characteristics of broilers and on incidence and level of salmonellae on prechill broiler carcasses. The FOS was fed at two levels (0 and .375%) in a complete factorial arrangement with two levels (0 and 55 mg/kg) of bacitracin methylene disalicylate (BMD) in nutritionally complete diets. Broilers were grown to 49 days of age, and samples were processed to determine dres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 8 publications
8
28
3
Order By: Relevance
“…With regard to other studies in the literature, results of this study are consistent in some instances and inconsistent in other. The lack of response in BWG and FCR of broilers fed CRP up to 4.5% of diet agrees with results of Waldroup et al (1993), Biggs et al (2007) and Rehman et al (2007Rehman et al ( , 2008 but fails to support the positive results of Ammerman et al (1988aAmmerman et al ( , 1988b, Yusrizal and Chen (2003), Xu et al (2003) and Rebolé et al (2010). The first broiler study by Ammerman et al (1989) evaluated the effect of feeding inulin-type fructans on broilers growth performance and noted that 3.75 g/kg FOS produced heavier birds at 47 d of age.…”
Section: Growth Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…With regard to other studies in the literature, results of this study are consistent in some instances and inconsistent in other. The lack of response in BWG and FCR of broilers fed CRP up to 4.5% of diet agrees with results of Waldroup et al (1993), Biggs et al (2007) and Rehman et al (2007Rehman et al ( , 2008 but fails to support the positive results of Ammerman et al (1988aAmmerman et al ( , 1988b, Yusrizal and Chen (2003), Xu et al (2003) and Rebolé et al (2010). The first broiler study by Ammerman et al (1989) evaluated the effect of feeding inulin-type fructans on broilers growth performance and noted that 3.75 g/kg FOS produced heavier birds at 47 d of age.…”
Section: Growth Performancesupporting
confidence: 89%
“…Similar results were also reported by Waldroup et al (1993). However, the studies performed by Yusrizal and Chen (2003) showed that adding chicory inulin and FOS at 10 g/kg diet improved carcass percentage and lowering the abdominal fat content in birds.…”
Section: Growth Performancesupporting
confidence: 83%
“…Some studies indicated a lack of a positive effect of inulin at inclusion from 4.0 to 20 g/kg Biggs et al, 2007;Rehman et al, 2007) or FOS at concentration from 3.75 to 20 g/kg in the basal diets (Biggs et al, 2007;Patterson et al, 1997;Waldroup et al, 1993) on broilers growth performance. In contrast, other authors have been reported the beneficial effect of inulin-type fructans on broilers growth performance (Ammerman et al, 1988(Ammerman et al, , 1989Kim et al, 2011;Li et al, 2008;Rebolé et al, 2010;Velasco et al, 2010;Xu et al, 2003;Yusrizal and Chen, 2003b) (Table 3).…”
Section: Effect Of Dietary Fructans On Growth Performance and Dietarymentioning
confidence: 99%
“…Broilers treated with 0.75% FOS had a four-fold reduction in the level of Salmonella typhimurium in the caeca (Bailey et al, 1991). Waldroup et al (1993) conducted two similar trials to evaluate the effect of 0.375% FOS on the incidence and level of contamination of Salmonella typhimurium on prechilled broiler carcasses. In the first trial, the addition of oligofructose resulted in a significant lower level of contamination of carcasses tested positive for Salmonella typhimurium, however, there were no significant differences among treatments in the replicated study.…”
Section: Effect Of Dietary Fructans On Microbial Population In Chickementioning
confidence: 99%
“…Van Leeuwen and Verdonk (2004) demonstrated improved growth and feed conversion in calves with prebiotics added to milk substitutes. In addition, in broilers challenged with salmonella, the FOS supplementation suppressed infections and a marked positive impact was observed on their development indices (Waldroup et al, 1993).…”
Section: Introductionmentioning
confidence: 99%